Evolution and biogeography of the Haploniscus belyaevi species complex (Isopoda: Haploniscidae) revealed by means of integrative taxonomy. Issue 1 (31st December 2022) - Knauber, Henry; Silberberg, Jona R.; Brandt, Angelika; Riehl, Torben
Abstract : The role of geomorphological features as drivers for benthic deep-sea biodiversity remains poorly understood. By disentangling the putative Haploniscus belyaevi Birstein, 1963a species complex from the abysso-hadal Kuril-Kamchatka Trench (KKT) region in the North-west Pacific Ocean, we aim to shed light on deep-sea differentiation and how it is related to potential bathymetric barriers such as the KKT and the Kuril-Island Ridge (KIR). Our integrative taxonomic approach featured morphological and molecular delimitation methods, also considering the post-marsupial development due to pronounced sexual dimorphism. Mitochondrial 16S and COI markers were sequenced and several molecular species delimitation methods were applied. By combining the different results we were able to delineate six distinct species within the belyaevi complex, including several morphologically cryptic species, and found hints of three additional species groups in the complex. Even though several of these species were distributed across the KKT and/or KIR, limited gene flow and depth-differentiation were indicated supporting previous notions that these geomorphological features play a role in deep-sea benthos speciation.